2004
DOI: 10.1051/animres:2004026
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of contagious bovine pleuropneumonia (CBPP) within-herd outbreaks for economic evaluation of local control strategies: an illustration from a mixed crop-livestock system in Ethiopian highlands

Abstract: -Contagious bovine pleuropneumonia (CBPP) is a respiratory disease of cattle caused by Mycoplasma mycoides subsp. mycoides small colony. CBPP is a major cause for concern in African countries (because of mortality, animal-production losses and cost of control). We present a simulation framework to compare economic efficiency of local (i.e., at the herd level) CBPP-control strategies (vaccination and antibiotic treatments). This framework was illustrated with data from an Ethiopian highlands cattle-smallholder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The fact that pastoralists did not regard treatment with antimicrobials (specifically oxytetracyclines) as a real cure for CBPP was demonstrated by the statements made by the pastoralists about treatment. This study has shown that there may be incorrect use of the antimicrobials as regards the dosages used and the routes and frequencies of treatment as also observed by Twinamasiko (2002) in Uganda and Lesnoff et al (2004) in Ethiopia. There is urgent need to communicate to the pastoralists the correct use of antimicrobials for CBPP control from recent findings of research in new antimicrobials.…”
Section: Discussionsupporting
confidence: 59%
“…The fact that pastoralists did not regard treatment with antimicrobials (specifically oxytetracyclines) as a real cure for CBPP was demonstrated by the statements made by the pastoralists about treatment. This study has shown that there may be incorrect use of the antimicrobials as regards the dosages used and the routes and frequencies of treatment as also observed by Twinamasiko (2002) in Uganda and Lesnoff et al (2004) in Ethiopia. There is urgent need to communicate to the pastoralists the correct use of antimicrobials for CBPP control from recent findings of research in new antimicrobials.…”
Section: Discussionsupporting
confidence: 59%
“…A mathematical model of CBPP is also used to compare economic efficiency of local (i.e., at the herd level) CBPP-control strategies (vaccination and antibiotic treatments). A study conducted in Ethiopian highlands cattle-smallholder system (Boji district, West Wellega Zone), with low CBPP virulence, revealed that antibiotics were the most economically efficient strategy than vaccination [4].…”
Section: Introductionmentioning
confidence: 99%
“…Transmission occurs through the inhalation of aerosolized infected droplets [240]. The role of subclinical carriers in transmission is uncertain [255,256]. Mycoplasma mycoides subsp.…”
Section: Contagious Bovine Pleuropneumoniamentioning
confidence: 99%